The possible “calming effect” of subchronic supplementation of a standardised phospholipid carrier-based Melissa officinalis L. extract in healthy adults with emotional distress and poor sleep conditions: results from a prospective, randomised, double-blinded, placebo-controlled clinical trial - Bano, Aasiya; Hepsomali, Piril; Rabbani, Fazle; Farooq, Umer; Kanwal, Ayesha; Saleem, Aisha; Bugti, Ali Akbar; Khan, Aftab Alam; Khalid, Zainab; Bugti, Mahroo; Mureed, Shah; Khan, Saeed; et al. (Frontiers in Pharmacology, 2023)
Background: Emotional distress conditions such as depression, anxiety, stress and poor sleep are widespread health problems that have a significant impact on people's lives. Conventional drugs are commonly prescribed to treat emotional distress and poor sleep conditions; however, these medications have several limitations and have shown multiple side-effects. Over recent years botanicals-based pharmacological agents have gained increasing research and clinical interest as possible treatment for emotional distress and sleep disorder. Of specific importance, Melissa officinalis L. (MO) leaf extract has demonstrated considerable neuropharmacological properties both in animal and human studies and has emerged as a promising 'calming agent'. However, research in this area is limited, and more studies are needed to validate its efficacy in emotional distress and poor sleep conditions.Objectives: We aimed to assess the pharmacological effects of sub-chronic supplementation of an innovative standardized phospholipids carrier-based MO aqueous extract on emotional distress and poor sleep conditions.Design: A 3-week, prospective, randomised, placebo-controlled, parallel-groups, double-blind clinical trial was conducted in 100 healthy adults complaining of a moderate degree of depression, or anxiety, or stress, i.e; score ≥14, ≥10, and ≥19, respectively, in the self-report Depression, Anxiety, and Stress Scale (DASS-42), or poor sleep as indicated by score of >5 in the Pittsburgh Sleep Quality Index (PSQI) scale. In addition, the impact of emotional distress and/or poor sleep on participants mental wellbeing, emotions and quality of life were also assessed using the self-report Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), Positive and Negative Affect Schedule (PANAS) scale, and Quality of life (WHO-QoL-BREF) scale.Results: Oral supplementation of 200 mg MO aqueous phospholipids-based extract (i.e., 400 mg/day) tablet twice a day for 3-weeks led to significant improvements in the depressive mood, anxiety, stress, positive and negative affect (emotional feelings), overall mental wellbeing, and quality of life scores (all ps<0.001). The MO extract treatment was well tolerated and no treatment-emergent effects, or serious adverse events were reported.According to the results of this study phospholipids carrier-based MO aqueous extract possess considerable neuropharmacological properties and its supplementation can provide a promising therapeutic option for the management of moderate emotional distress and/or poor sleep conditions.